A novel vertical elastic vibration reduction for railway vehicle carbody based on minimum generalized force principle. (15th April 2023) - Li, Fansong; Yang, Sheng; Yang, Zhenhuan; Shi, Huailong; Zeng, Jing; Ye, Yunguang
Abstract: Aiming at the vertical elastic vibration reduction of a railway vehicle carbody, the traditional technology mainly focuses on the design of modal frequency, the method of increasing damping and the design of dynamic vibration absorber (DVA), with little attention to the design of modal shape. In this paper, a novel vertical elastic vibration reduction method based on the minimum generalized force principle (MGFP) is proposed, i.e., the vertical elastic vibration of carbody is reduced by adjusting its own parameters (weight distribution and stiffness distribution) to control the first-order vertical bending (FVB) modal shape nodes to the carbody–bogie interface positions. Firstly, to better apply MGFP, a factor called generalized force factor (GFF) that can determine the level of generalized force (GF) is proposed. By improving theoretical model of a railway vehicle carbody, the traditional uniform cross-section Euler–Bernoulli beam (UCEB) is replaced by variable cross-section Euler–Bernoulli beam (VCEB) model, and the influencing factors of modal frequency and modal shape node locations can be investigated by the VCEB model. Then, the vertical vehicle system dynamics model is established based on the VCEB carbody model, and the influence of weight distribution, stiffness distribution and carbody–bogie interface positions on the elastic vibration is analyzed under a sweep frequency signal and track irregularities. Finally, the vibration reduction method is verified by a full-scale roller rig test. The theoretical analysis and experimental results show that: by changing the weight distribution or stiffness distribution of the carbody, the FVB modal shape node locations can be effectively controlled, and then combined with the design of carbody–bogie interface positions, the vertical bending elastic vibration of the carbody can be reduced. The vibration reduction method proposed in this paper can be applied to the design of new carbodies or the layout optimization of carbody subsidiary mass. Highlights: A novel vibration reduction method based on MGFP is proposed for railway carbody. A railway vehicle dynamics model which considering carbody as VCEB is derived. A generalized force factor is proposed to determine the generalized force level. The effectiveness of the vibration reduction method is verified by a roller rig test.